Purchasing behaviour of UiTM Sabah students on soap / Qadaffy M. T. Aidala - Aidala, Qadaffy M. T. (2006)
Soap is a production formulation of which is specially devised to promote the development of soap. Soap was usually used to clean and protect body from germs. Nowdays, there are so many types of soap in the market. They can be in term of liquid and bar soap. In this study this research conducts to identify the purchasing behavior on soap among the UITM Sabah students.